Prevalence of physical and mental health problems among internally displaced persons in White Nile state, Sudan 2023: a cross sectional study - Ahmed Mohamed Ahmed Ali; Omran Aldoma Mohammed Adam; Sara Eltayeb Mustafa Salem; Sara Hamad Ibrahim Hamad; Nosiba Elnair Musa Ahmed; Hassan Mohamed Ahmed Ali; Aseel Abass Mohamed Abass; Hiba-Allah Abass Mohamed Abass; Abubaker Izz-Eldein Albasher; Mawada Eltagi Elsayid Yousif; Fadwa Elfadil Ahmed Abdalla; Osman AlShazly Osman Abd-alaziz; et al. (BMC Public Health, 2024)
Abstract Background Following the latest war in 2023, over nine million people have been internally displaced, of which White Nile State received over 50,000. They lived in different camps and moved to big cities. This study assessed the scope of mental and physical concerns among the IDPs to identify important healthcare needs. Methods This is a cross-sectional survey of four localities of internally displaced persons in White Nile state, Sudan. Between December 4th and December 14th, 2023, 800 directly interviewed participants were randomly selected using a face-to-face semi-structured interview. Potential participants were determined using a stratified simple random method. Results The findings revealed that 45% of IDPs experienced poor physical health, with prevalent ailments among adults including minor colds (67%), respiratory infections (43%), prolonged flu episodes (36%), insomnia (38%), headaches (42%), gastric upset (44%), nausea (35%), and gastrointestinal issues (40%). Depression, PTSD, and anxiety were prevalent among adults at rates of 18%, 20%, and 14% respectively. Moreover, a staggering 72% of children under five suffered from malnutrition, with males accounting for 44% and females 56%. Conclusion Alarming numbers of IDPs in White Nile State face significant physical and mental health problems, warranting urgent interventions from local and international relief agencies.